Determinants of corporate environment, social and governance (ESG) reporting among Asian firms - Rashida Abdul Rahman; Maha Faisal Alsayegh (Journal of Risk and Financial Management, 2021)
Departing from previous studies, which have mostly focused on Western countries, our work investigates the determinants of the corporate environment, social and governance (ESG) reporting among Asian firms. Examining Asian public listed firms from 2005 to 2017, our cross-sectional model results indicate that firm characteristics (economic performance, profitability, leverage and size) are found to disclose additional ESG information. The outcome is consistent with the legitimacy theory, which posits that firms provide higher ESG reporting to legitimize and justify the firm's continuous existence. The findings are important for firms, stakeholders and policymakers. While firms may formulate ways to improve ESG reporting to compete in the international market, the stakeholders may pressure firms to disclose more information on ESG and policymakers to designalegal framework on ESG that suits firms in Asia.
Keywords: 330; Asian companies; corporate sustainability reporting; determinants; economic performance; environment; governance; social